The Taiwan issue and its impacts on China's ties with the United States and Japan. - Lim, Ryan Ruey Yan. (2008)
The relationship between China, the United States and Japan has become an important factor in the international relations and security issues in East Asia after the end of the Cold War and the dissolution of the Soviet Union. In this triangular relationship, the Taiwan issue, the legacy of the Chinese civil war more than 50 years ago, remains a contentious issue in China's relations with the US and Japan. This dissertation will look at the strategic value of the Taiwan issue to three both countries and its impact on China's ties with the US and Japan. It will then conclude with a brief assessment of the of the outlook of China's ties with both countries vis-a-vis the Taiwan issue.